2021
DOI: 10.3389/fendo.2021.601960
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of TSH Stimulation Level, Stimulated Tg Level and Tg/TSH Ratio on the Therapeutic Effect of 131I Treatment in DTC Patients

Abstract: PurposeTo study the influences of pre-ablation TSH stimulation level, sTg and sTg/TSH ratio on the therapeutic effect of the first 131I treatment in DTCs.MethodsAccording to the thyroid stimulating hormone (TSH) levels (mU/l), all the 479 differentiated thyroid cancer (DTC) patients were divided into two groups: TSH < 30 and TSH ≥ 30. The TSH ≥ 30 group was divided into three subgroups: 30 ≤ TSH < 60, 60 ≤ TSH < 90 and TSH ≥ 90. The clinical features and the therapeutic effects of the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
2
6
0
1
Order By: Relevance
“…In this study, we found that patients with higher sTg levels were more likely to have non-ER. sTg critical value for predicting non-ER was 4.7 µg/L, with an area under the curve of 0.922, a sensitivity of 90.38%, and a speci city of 81.16%, which was close to the previously reported data [27][28][29][30]. However, sTg may be more accurate when corrected by TSH, because Tg levels are signi cantly affected by thyrotropic stimulation of TSH on the thyroid remnant [5].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, we found that patients with higher sTg levels were more likely to have non-ER. sTg critical value for predicting non-ER was 4.7 µg/L, with an area under the curve of 0.922, a sensitivity of 90.38%, and a speci city of 81.16%, which was close to the previously reported data [27][28][29][30]. However, sTg may be more accurate when corrected by TSH, because Tg levels are signi cantly affected by thyrotropic stimulation of TSH on the thyroid remnant [5].…”
Section: Discussionsupporting
confidence: 83%
“…A retrospective study revealed that patients with sTg > 18 ng/ml and sTg/TSH > 0.35 before RAI therapy were signi cantly associated with unsuccessful ablation [31]. Another study indicated that the sTg < 9.51 ng/ml and sTg/TSH < 0.11 predicted a better therapeutic outcome [30]. In this study, we found that, like sTg, the sTg/TSH ratio was strongly correlated with the therapeutic response.…”
Section: Discussionsupporting
confidence: 54%
“…A retrospective analysis revealed that the ps-Tg level <8.55 ug/L before ablation predicted 88% sensitivity and 72% specificity for disease remission following 18-24 months of 131 I therapy (18). Zheng et al (19) demonstrated that the ps-Tg level <9.51 ug/L indicated better efficacy of 131 I treatment in patients with DTC. The present study found that a cut-off value of 6.915 ug/L predicted ER, which is similar to the results of the abovementioned past studies.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery, selective radioiodine therapy (RAIT) after total thyroidectomy (TT) and thyroid stimulating hormone (TSH) sup-pressive therapy are the standard treatments for DTC [1]. As a speci c tumor marker for long-term follow-up after RAIT in DTC, serum thyroglobulin (Tg) can predict DTC persistence, distant metastasis or recurrence [2,3,4]. However, the Tg level can be affected by antithyroglobulin antibody (TgAb), which made Tg measurement becomes unreliable.…”
Section: Introductionmentioning
confidence: 99%